2016
DOI: 10.15430/jcp.2016.21.4.209
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Lipid Metabolic Reprogramming as Anticancer Therapeutics

Abstract: Cancer cells rewire their metabolism to satisfy the demands of growth and survival, and this metabolic reprogramming has been recognized as an emerging hallmark of cancer. Lipid metabolism is pivotal in cellular process that converts nutrients into energy, building blocks for membrane biogenesis and the generation of signaling molecules. Accumulating evidence suggests that cancer cells show alterations in different aspects of lipid metabolism. The changes in lipid metabolism of cancer cells can affect numerous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 52 publications
0
33
0
Order By: Relevance
“…Transformed cells possess the capability of adjusting their metabolic demands toward the synthesis of macromolecules, mainly lipids for biogenesis of membranes and various signaling cues, in order to sustain their high proliferative rates . However, more unusual is their absolute dependency on de novo lipid synthesis, which thereby highlights an attractive metabolic addiction of the cancer cells . This metabolic predisposition might be exploited in multiple arenas for effective cancer therapeutics.…”
Section: Moving Forwardmentioning
confidence: 99%
“…Transformed cells possess the capability of adjusting their metabolic demands toward the synthesis of macromolecules, mainly lipids for biogenesis of membranes and various signaling cues, in order to sustain their high proliferative rates . However, more unusual is their absolute dependency on de novo lipid synthesis, which thereby highlights an attractive metabolic addiction of the cancer cells . This metabolic predisposition might be exploited in multiple arenas for effective cancer therapeutics.…”
Section: Moving Forwardmentioning
confidence: 99%
“…The cancer cells exploit lipid metabolic pathways in order to fulfil their demand for energy as well as biosynthetic precursors. Aberrations in lipid metabolism thus affects numerous cellular processes such as cell growth, proliferation, differentiation and cell survival 1 . Sphingolipids (SPLs), apart from the inceptive view of being considered as mere structural components, have evolved as crucial regulators of myriads of cellular functions.…”
mentioning
confidence: 99%
“…Observations have shown that rapid growth of cancer cells requires a sustainable supply of lipids for membrane formation. In view this, cancer cells have to enhance the uptake of lipids or activate de novo lipid synthesis which has been observed in many tumor types, including HCC . For instance, the observations showed high expressions of Fasn and Acly genes whose products are lipid metabolic pathway‐involved enzymes in cancer cells .…”
Section: Discussionmentioning
confidence: 95%